1993
DOI: 10.1111/j.1365-3083.1993.tb01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV‐Positive Sera on the Functional Activity of Polymorphonuclear Neutrophils from Healthy Donors

Abstract: The impact of the sera from 64 HIV-1-infected patients on the functional activity of polymorphonuclear neutrophils (PMN) from 9 healthy donors was investigated. Augmentation of PMN oxygen radical production in the presence of sera from HIV-infected patients (PMN chemiluminescence) was demonstrated. This enhancement was connected with intracellular generation of chemiluminescence (CL). A significant correlation between this enhancement and stages of HIV infection was not found. The presence of the sera from HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Phagocytic function has been reported as subnormal [17], supranormal [18], oxidative function as excessive [19] and impaired [20], and bacterial killing as reduced [21] and unchanged [22]. Two studies have suggested that heat-labile soluble serum factors may play an important part in HIV-associated neutrophil dysfunction [23,24]. The one functional test which appears to be impaired in all studies is chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytic function has been reported as subnormal [17], supranormal [18], oxidative function as excessive [19] and impaired [20], and bacterial killing as reduced [21] and unchanged [22]. Two studies have suggested that heat-labile soluble serum factors may play an important part in HIV-associated neutrophil dysfunction [23,24]. The one functional test which appears to be impaired in all studies is chemotaxis.…”
Section: Discussionmentioning
confidence: 99%